2008
DOI: 10.1002/ijc.23430
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities and oral cancer risk: A systematic review and meta‐analysis of case‐control studies

Abstract: There is uncertainty and limited recognition of the relationship between socioeconomic inequalities and oral cancer. We aimed to quantitatively assess the association between socioeconomic status (SES) and oral cancer incidence risk. A systematic review of casecontrol studies obtained published and unpublished estimates of the SES risk related to oral cancer. Studies were included which reported odds ratios (ORs) and corresponding 95% CIs of oral cancer with respect to SES, or if the estimates could be calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
221
1
30

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(280 citation statements)
references
References 80 publications
13
221
1
30
Order By: Relevance
“…Alcohol consumption has been linked to periodontitis 19 and tooth wear 20 and both smoking and alcohol are closely linked to the incidence of oral cancer. 21 The incidence of oral cancer is also strongly related to social and economic deprivation, 22 particularly for men, and this widening inequalities gap makes it all the more important that all avenues to address possible risk factors are explored. All patient examinations in the CDS include smoking and alcohol cessation advice related to risks of oral disease and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption has been linked to periodontitis 19 and tooth wear 20 and both smoking and alcohol are closely linked to the incidence of oral cancer. 21 The incidence of oral cancer is also strongly related to social and economic deprivation, 22 particularly for men, and this widening inequalities gap makes it all the more important that all avenues to address possible risk factors are explored. All patient examinations in the CDS include smoking and alcohol cessation advice related to risks of oral disease and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Low socioeconomic status has been significantly associated with an increased oral cancer risk in high and lower income-countries (Conway, 2008). These groups often have less access to the health services and health education that would empower them to make decisions to protect and improve their own health.…”
Section: 5 Socioeconomic Statusmentioning
confidence: 99%
“…26 However, it is worth reflecting on the role of socio-economic deprivation as a growing literature identifies this as an important determinant of oral cancer. 27 Poverty still undoubtedly has a role to play in both the likelihood of developing the disease and the manner in which patients from more disadvantaged groups negotiate the healthcare system and are treated by health professionals. Munro 28 has suggested that deprivation makes some patients more vulnerable not only to developing cancer but also to experiencing a delay in their diagnosis, problems in communicating with professionals, an increased risk of complications and poorer treatment outcomes.…”
Section: Patient Characteristicsmentioning
confidence: 99%